DEMYSTIFYING STUDENTS’ WRITING ERRORS IN DESCRIPTIVE TEXT AFTER THE IMPLEMENTATION OF THINK-TALK-WRITE (TTW) STRATEGY - Rahma Juwita, Andini; Wachyudi, Kelik; Dafitri, Fela (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to identify the types and frequencies of writing errors in students' descriptive texts produced after the implementation of the Think-Talk-Write (TTW) strategy in a rural senior high school. Writing is still a difficult productive skill for Indonesian learners of English, and error analysis studies are generally carried out without being linked to a particular teaching strategy, so it is not yet clear which error types remain dominant once a strategy such as TTW has been applied. This research used a qualitative descriptive case study design. The data were collected through a semi-structured interview with the English teacher and the analysis of twenty two descriptive texts produced by tenth grade students across two TTW sessions. The errors were classified using Dulay, Burt, and Krashen's (1982) surface strategy taxonomy. From forty two identified errors, omission was the most dominant type at 54.8 percent, followed by misformation and addition at 16.7 percent each, and misordering at 11.9 percent. The dominance of omission, especially the missing copula to be, is interpreted as first language interference. The study also found a gap between the teacher's perception and the actual error pattern in the students' texts. These findings provide a contextual reference for teaching descriptive writing in rural schools.